Prospect of using rice straw for power generation: a review - Logeswaran J.; Shamsuddin A.H.; Silitonga A.S.; Mahlia T.M.I. (Springer, 2023)
biomass; biomass burning; carbon dioxide; demand analysis; domestic work; environmental impact; fossil fuel; management practice; methane; nonrenewable resource; power generation; rice; straw; Malaysia; agriculture; Asia; Malaysia; Oryza; soil; Agriculture; Asia; Malaysia; Oryza; Soil